Computer-Mediated reading and its impact on learners' reading comprehension skills - Dumanig, F.P.; David, M.K.; Jubilado, R. (2011)
Teaching reading is not an easy skill as most students today easily get bored of reading written texts in books and other traditional reading materials. With the emergence of technology and its fast development, educators have integrated the use of computers in teaching reading. Due to technological breakthrough, a study on computer-mediated reading and its impact on the reading comprehension skills of learners of English as a Second Language (ESL) is discussed. This study uses an experimental research design to determine the Impact of computer-mediated reading on students' reading comprehension skills. A total of 140 freshmen engineering students at Mapua Institute of Technology, Philippines took part in the study. To carry out the study, the participants were divided into an experimental and a control group The findings of the study reveal that the use of computer-mediated reading results in a significant improvement In students' reading comprehension skills. The findings are supported by statistical computations using the independent t-test in determining the significant difference in the pre and posttest results of the two groups. After exposing them to the treatment significant learning is acquired by those in the experimental group as compared to those in the control group. The study shows that computer-mediated reading creates a significant impact on students' reading comprehension skills specifically in following directions, noting details, sequencing events, getting the main idea, making inferences and making generalizations On account of the significant findings of the study, it is recommended that teachers should use computers in the reading classroom